(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Success in the formation of the communicative competence of future teachers is a title awarded for the fact that they have trained dozens, hundreds of students, bringing their profession to the level of art. Or the training of specialists who look at this or that world in a new way, are able, know the eye of work, build and elevate the foundation of our great future-the most important and responsible task facing the teachers of our republic.